Adrenomyeloneuropathy in a subacute combined degeneration suspect: a diagnostic dilemma - Saxena, Sumanyu; Khalid, Atahar (International Journal of Advances in Medicine, 2022)
Adrenomyeloneuropathy (AMN) is a variant of adrenoleukodystrophy (ALD) which is a peroxisomal disorder of beta-oxidation that results in accumulation of very long-chain fatty acids (VLCFAs) in plasma, central and peripheral nervous systems, adrenal glands and testes leading to their dysfunction. These conditions are known as the ALD/AMN complex. In this article we discuss a case of AMN with respect to clinical presentation, diagnosis and treatment.